Potter’s syndrome: a case report - ., Latika; Nanda, Smiti; Singhal, Savita; Chahal, Amandeep (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Potter’s syndrome is a rare congenital disorder characterized by characteristic atypical appearance of a newborn due to the oligohydroamnios experienced during the intrauterine life. Its incidence varies from 1 in 2000 to 1 in 5000. 40 years old G7P4L1 A2 at 37 weeks of period of gestation was admitted at a tertiary care institute with labour pains. Her previous obstetric history included three full term vaginal deliveries, two of the babies expired in postnatal period of 2 months and 7 days age respectively. One was alive and healthy. In fourth pregnancy she underwent emergency LSCS, but baby expired 5 months after birth. She had history of 2 abortions which were spontaneous and not followed by curettage. She also gave history of intake of some drugs at 6th week of gestation prescribed by a local Baba to have a male child. Her ultrasonography revealed fetus with bilateral renal agenesis. On per abdomen examination, clinically liquor was very much reduced, Fetal heart sounds were not heard. She delivered vaginally a still born fetus with ambiguous genitalia, anal atresia and malformed limbs. The fetus had typical facial appearance of “potter facies”. Potter’s Syndrome or Sequence is a rare fatal disorder. Apart from typical Potter’s facies, pulmonary hypoplasia, skeletal deformities are associated with this condition, severity depends on the degree and duration of oligohydramnios. Therefore, it is very important to pick up this condition during antenatal ultrasound at earlier gestation so that timely decision regarding further workup and pregnancy termination can be undertaken. This case report emphasizes upon the importance of regular antenatal check ups and examination in each and every patient as it picks up the suspicious cases which can lead to further workup, definite diagnosis of the condition and timely decision regarding management.